1999
DOI: 10.1055/s-2007-979222
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Olanzapine-lnduced Reversible Neutropenia

Abstract: Olanzapine is a tricyclic neuroleptic agent that due to structural similarities was expected to be a safe alternative to clozapine, which has a 0.5-2% risk of agranulocytosis. So far, only rare cases of leukocytopenia and thrombocytopenia have become known. In the association, "Drug Safety in Psychiatry", which is made up of 25 German psychiatric hospitals, two cases of olanzapine-induced neutropenia occurred in patients with chronic schizophrenia. The adverse drug reaction was noticed 17 days after the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 3 publications
0
9
1
Order By: Relevance
“…For example, it has been reported that chlorpromazine's risk of agranulocytosis is 0.13%, 45 while a recent study estimated the risk for olanzapine in this regard to be 0.15%. 46,47 In summary, clozapine registries and their associated compulsory blood monitoring systems (no blood, no drug) have established their effectiveness in reducing both the incidence of clozapine-induced agranulocytosis and associated mortality rates.…”
Section: Clozapine Agranulocytosis and Mortalitymentioning
confidence: 99%
“…For example, it has been reported that chlorpromazine's risk of agranulocytosis is 0.13%, 45 while a recent study estimated the risk for olanzapine in this regard to be 0.15%. 46,47 In summary, clozapine registries and their associated compulsory blood monitoring systems (no blood, no drug) have established their effectiveness in reducing both the incidence of clozapine-induced agranulocytosis and associated mortality rates.…”
Section: Clozapine Agranulocytosis and Mortalitymentioning
confidence: 99%
“…In contrast, a number of studies that specifically studied patients with clozapine-induced white blood cell abnormalities did not find any problems with white blood cell counts after switching these patients to olanzapine (Steinwachs et al 1999;Beasley et al 1997;Loeffler et al 2003). Kodesh et al (2001) suggest that leucopenia during olanzapine treatment may be a dose-dependent phenomenon, because leucopenia disappeared with a dose decrease in the three patients they described.…”
Section: Discussionmentioning
confidence: 91%
“…It has been discussed controversially whether olanzapine also has a potential to induce neutropenia and agranulocytosis. Up to now, seven case reports of haematopoetic disturbances during olanzapine treatment have been published, including one case of olanzapine-induced agranulocytosis (Naumann et al 1999), two cases of neutropenia (Steinwachs et al 1999) and one leucopenia (Meissner et al 1999). We report three subjects with reversible neutropenia under olanzapine, with rapid normalisation of neutrophil cell counts after discontinuation of olanzapine.…”
mentioning
confidence: 90%
“…1,2 Although known to produce side effects such as weight gain and metabolic syndrome, a lesser studied phenomenon associated with Olanzapine therapy is granulocytopenia. [3][4][5] This phenomenon is usually associated with Clozapine, a second-generation antipsychotic. 6 Several mechanisms have been proposed as being responsible for the neutropenia generated by these drugs.…”
Section: Introductionmentioning
confidence: 99%